Novel coordination compounds featuring 9-chloro-9-phosphaalkenylchloro-9-germafluorene ligands. (15th July 2022) - Deak, Noemi; Septelean, Raluca; Buta, Lavinia; Moraru, Ionut-Tudor; Cretoiu, Iulia Andreea; Soran, Albert; Nemes, Gabriela
Graphical abstract: Coordination study of 9-chloro-9-phosphaalkenylchloro-9-germafluorene fragment containing derivatives towards transition metals such as gold or palladium was carried out. The new complexes were fully characterized in solution by multinuclear NMR and in solid state by X-ray diffraction. Abstract: A comprehensive experimental/theoretical study was carried out on derivatives containing the 9-chloro-9-phosphaalkenylchloro-9-germafluorene fragment, in order to assess their stability upon coordination to transition metals such as gold or palladium. Complexes were fully characterized in solution by multinuclear NMR and in solid state by X-ray diffraction. An extensive study on the solid state molecular structures of the gold and palladium phosphaalkenyl germanium complexes is presented following different intermolecular associations. Density functional theory (DFT) calculations coupled with natural bond orbital (NBO) techniques were performed to shed further light on the structural features, the strength of intramolecular interaction and the bonding phenomena occurring within targeted molecules.